The Effect of Propolis on Th1/Th2 Cytokine Expression and Production by Melanoma-bearing Mice Submitted to Stress - Missima, F. [UNESP]; Pagliarone, A. C. [UNESP]; Orsatti, C. L. [UNESP]; Araujo, J. P. [UNESP]; Sforcin, J. M. [UNESP] (Wiley-Blackwell, 2010)
Since propolis possesses immunomodulatory and antitumoral activities, this work aimed to evaluate its effect on Th1 (IL-2 and IFN-gamma) and Th2 (IL-4 and IL-10) cytokines mRNA expression and production by melanoma-bearing mice submitted to immobilization stress. C57BL/6 male mice were inoculated with B16F10 cells, treated with propolis and submitted to stress for 14 days. Spleen cells were assessed for Th1/Th2 cytokine expression and production. Stress induced a higher tumor area, while propolis-treated mice, stressed or not, showed a melanoma development similar to the control. In groups without melanoma, stress or propolis treatment did not affect IL-2, IL-4 and IL-10 gene expression. on the other hand, IL-2 and IL-10 expression was inhibited in melanoma-bearing mice, stressed or not. Th1 cytokine production was also inhibited in melanoma-bearing mice. Propolis administration to melanoma-bearing mice submitted to stress stimulated IL-2 expression, as well as Th1 cytokine (IL-2 and IFN-gamma) production, indicating the activation of antitumor cell-mediated immunity. Propolis also stimulated IL-10 expression and production, which may be related to immunoregulatory effects. The data indicate that propolis exerted an immunomodulatory activity in this assay, which may be related to its antitumoral action in vivo. Copyright (c) 2010 John Wiley & Sons, Ltd.
Keywords: Stress; Melanoma; Cytokines; Propolis; Immunomodulation